Moodle as a supplementary tool in the teaching at the University of the Philippines Los Banos (UPLB) - Dimasuay, Lynie B. (UP Los Baños Journal, 2012)
The use of learning or content management system in teaching as an e-learning software platform is prevalent nowadays. One very popular open source software worldwide is the Modular Object Oriented Dynamic Learning Environment (MOODLE). For the past three years, faculty members of the University of the Philippines Los Banos (UPLB) have been using MOODLE to augment face-to-face teaching. This study was conducted to assess the popularity and usefulness of MOODLE among UPLB students. Students of Math 11, SF 120, FST 111 served as respondents and were asked to answer a questionnaire composed of 15 items with 5 choices in each item about the features of MOODLE and how it can enhance a student's learning. Results showed the majority of the respondents in the four courses believed that MOODLE Is an asset to their course. Its interactive features such as online class resources, information updates, discussions and forum, and quizzes helped them in their learning progress in class. Based on the reason cited, students could easily access their lecture materials and other reading assignments. They could also catch up with the lessons and check on the requirements of the course. Because MOODLE can also provide venue for the interaction between teachers and students as well as among students, it facilitated easier communication. Thus, students' interaction aws also enhanced. Moreover, the respondents agreed that MOODLE was user friendly, easy to navigate and accessible. However, some respondents were undecided to the accessibility and the ease of using its interactive features. Technical problems in the main server due to brown-outs or network bandwidth may have contributed to their unfavorable feedback. Despite the benifits that MOODLE offers, its use as a tool in teaching is not yet popular among both the faculty and students to the benifits of MOODLE. Also, policies can be made and implemented in the future on facilitating conditions for a successful e-learning program.